Efficacy of IAPP suppression in mouse and human islets by GLP-1 analogue conjugated antisense oligonucleotide - Gurlo, Tatyana; Prakash, Thazha P.; Wang, Zhongying; Archang, Maani; Pei, Lina; Rosenberger, Madeline; Pirie, Elaine; Lee, Richard G.; Butler, Peter C. (Frontiers in Molecular Biosciences, 2023)
Insulin resistance is the major risk factor for Type 2 diabetes (T2D). In vulnerable individuals, insulin resistance induces a progressive loss of insulin secretion with islet pathology revealing a partial deficit of beta cells and islet amyloid derived from islet amyloid polypeptide (IAPP). IAPP is co-expressed and secreted with insulin by beta cells, expression of both proteins being up regulated in response to insulin resistance. If IAPP expression exceeds the threshold for clearance of misfolded proteins, beta cell failure occurs exacerbated by the action of IAPP toxicity to compromise the autophagy lysosomal pathway. We postulated that suppression of IAPP expression by an IAPP antisense oligonucleotide delivered to beta cells by the GLP-1 agonist exenatide (eGLP1-IAPP-ASO) is a potential disease modifying therapy for T2D. While eGLP1-IAPP-ASO suppressed mouse IAPP and transgenic human IAPP expression in mouse islets, it had no discernable effects on IAPP expression in human islets under the conditions studied. Suppression of transgenic human IAPP expression in mouse islets attenuated disruption of the autophagy lysosomal pathway in beta cells, supporting the potential of this strategy.